2020
DOI: 10.3389/fpsyt.2019.00992
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Value of Cell-Free DNA Based on Alu in Psychiatric Disorders

Abstract: Psychiatric disorders impose a huge burden on individuals, families, and society. The Alu repeat sequence is a member of the short interspersed nuclear element (SINE) family of mammalian genomes, however, its expression pattern and role in psychiatric disorders is unclear. The current paper aimed at determining the concentrations of Alu in patients with schizophrenia (SZ), major depressive disorder (MDD), and alcohol-induced psychotic disorder (AIPD), and to further define the role and value of Alu as a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…However, they were also excluded because two reports were not enough to conduct a meta-analysis for this type of cfDNA (see further). For the same reason, one report on cf-gDNA was excluded from the DDs group [ 36 ], as the remaining studies analyzed cf-mtDNA. Ultimately, the following numbers of reports were included in the meta-analysis: schizophrenia, 8 [ 24 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; BD, 4 [ 25 , 35 , 43 , 44 ]; DDs, 5 [ 35 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they were also excluded because two reports were not enough to conduct a meta-analysis for this type of cfDNA (see further). For the same reason, one report on cf-gDNA was excluded from the DDs group [ 36 ], as the remaining studies analyzed cf-mtDNA. Ultimately, the following numbers of reports were included in the meta-analysis: schizophrenia, 8 [ 24 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; BD, 4 [ 25 , 35 , 43 , 44 ]; DDs, 5 [ 35 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the same reason, one report on cf-gDNA was excluded from the DDs group [ 36 ], as the remaining studies analyzed cf-mtDNA. Ultimately, the following numbers of reports were included in the meta-analysis: schizophrenia, 8 [ 24 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; BD, 4 [ 25 , 35 , 43 , 44 ]; DDs, 5 [ 35 , 45 , 46 , 47 , 48 ]. The total number of individual studies included in the meta-analysis was sixteen because some reports considered several diseases simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies reported a two- to three-fold c-cfDNA increase in SZ patients. The concentrations of mtDNA [ 38 ], rDNA [ 7 ], GC-rich Alu repeats [ 50 ], and oxy-DNA [ 6 ] in the blood plasma of SZ patients exceeded the concentrations in the blood plasma of healthy controls (hc-cfDNA).…”
Section: Introductionmentioning
confidence: 99%
“…The increased plasma levels of gc-DNA and oxy-DNA suggest that sz-cfDNA is a biologically active molecule. For example, the authors [ 50 ] found a positive relationship between the contents of Alu and interleukin-1β and interleukin-18 in SZ patients. However, a priori, we cannot determine what could be responsible for the potential biological activity of sz-cfDNA: a high concentration of c-cfDNA fragments or an altered composition of sz-cfDNA compared to hc-cfDNA fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Однако в литературе мало сведений об изменении концентраций вкДНК у больных с психозами. Было показано, что концентрации вкДНК возрастают в плазме крови китайских больных шизофренией [13,14]. Авторы этого исследования ранее на небольшой выборке также обнаружили, что концентрации вкДНК возрастают в плазме крови нелеченых больных шизофренией [15,16].…”
unclassified